Language in the Metaverse: A Study on Social Interaction, Identity Formation, and Reality Construction in Immersive Virtual Environments - Khoiriyah, Khoiriyah; Costa, Bruna; Rocha, Thiago (Journal International of Lingua and Technology, 2025)
The metaverse, an immersive virtual environment that blends augmented and virtual reality, is rapidly gaining popularity as a space for social interaction and digital identity formation. As users engage in these virtual spaces, language plays a critical role in shaping interactions, constructing identities, and influencing perceptions of reality. This study explores how language is used in the metaverse to facilitate social interactions, contribute to the formation of virtual identities, and impact users’ construction of reality in these immersive environments. The primary objective of this research is to examine how language functions in the metaverse, focusing on the role of communication in virtual spaces for socializing, self-representation, and the construction of a shared virtual reality. Using a mixed-methods approach, this study combines qualitative interviews with metaverse users and quantitative analysis of language use in virtual environments. The results indicate that language in the metaverse plays a fundamental role in building social connections, creating and negotiating identities, and constructing a sense of reality in the virtual world. Users reported that the language used in the metaverse helps them define their virtual selves, interact with others, and navigate the complexities of the virtual space. This study concludes that language is not only a tool for communication but also a powerful medium for shaping both virtual identities and perceptions of reality in immersive environments.